Numerical simulation of hybrid composite tubes under oblique compression - Ismail, Al Emran; Nezere, N. (Emerald Insight, 2017)
Purpose – An energy-absorbing device is an important tool that is capable of increasing the survivability of passengers in vehicles. Generally, empty metallic tubes are used, and it is found that the energy absorption capability is lower than the energy obtained using composite materials. Therefore, this paper numerically presents the crushing performances of hybrid tubes under axial and oblique compressions. Design/methodology/approach – Three important parameters are used such as fiber thicknesses, fiber orientations and oblique compression angles. Epoxy-reinforced fibers are wrapped around the steel tubes and it is then modeled numerically using the ANSYS finite element program. Belytscho – Tsay shell element is used to model the composites, while a bilinear kinematic hardening model is used to model the steel tube. A proper contact algorithm is implemented to prevent interpenetration among elements and surfaces. Findings – A proper contact algorithm is implemented to prevent interpenetration among elements and surfaces. Hybrid tubes are quasi-statically crushed and force– displacement curves are extracted and analyzed. Originality/value – It is found that the introduction of oblique compressions has induced bending moments and therefore decreases the energy absorption capability. Varying fiber orientations also insignificantly changed the crushing performances. However, wrapping carbon/epoxy composite that is capable of strengthening the tubes, is also subjected to oblique compression compared with the glass/epoxy composites.